2013
DOI: 10.1017/s1366728913000023
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of semantic processing is shaped by exposure to specific mother tongues: The case of insight problem solving by bilingual and monolingual native Hebrew speakers

Abstract: Solving insight problems is a complex task found to involve coarse semantic processing in the right hemisphere when tested in English. In Hebrew, the left hemisphere (LH) may be more active in this task, due to the inter-hemispheric interaction between semantic, phonological and orthographic processing. In two Hebrew insight problems experiments, we revealed a performance advantage in the LH, in contrast to the patterns previously observed in English. A third experiment, conducted in English with early Hebrew-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To examine this topic more directly, future research may compare between different language pairs in the same study. To rule out the possibility that the effects observed in the second language are attributable to the unique features of that language rather than to processing in a second language, monolingual speakers of that language should be also included (for a similar design, see Mashal et al, 2015; Metuki et al, 2013). Another interesting extension of our study would be looking at metaphoricity as a continuum instead of a dichotomy, as we chose, which may increase analysis sensitivity of hemispheric contributions (e.g., Lai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To examine this topic more directly, future research may compare between different language pairs in the same study. To rule out the possibility that the effects observed in the second language are attributable to the unique features of that language rather than to processing in a second language, monolingual speakers of that language should be also included (for a similar design, see Mashal et al, 2015; Metuki et al, 2013). Another interesting extension of our study would be looking at metaphoricity as a continuum instead of a dichotomy, as we chose, which may increase analysis sensitivity of hemispheric contributions (e.g., Lai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Early exposure to two languages can influence lateralization patterns if languages are also structured differently. When English was tested in bilinguals with L1 -Hebrew and L2 -English, who learned both languages very early showed an advantage of the left hemisphere while performing a semantic task where monolingual Hebrews also demonstrate an advantage in the left hemisphere but the monolingual English showed an advantage of the right hemisphere [3,909]. Metuki et al suggested that Hebrew has the linguistic characteristics that affect the lateralization of semantic processing in Hebrew affect how bilingual participants processed a task in English.…”
Section: роль нейролингвистических исследований в процессе изучения билингвизмаmentioning
confidence: 99%
“…Early exposure to two languages may influence lateralization patterns when the languages are differently structured as well. When tested in English, highly proficient Hebrew-English bilinguals who learned both languages very early showed a left-hemisphere advantage for a semantic task in which Hebrew monolinguals also show a left-hemisphere advantage, but for which English monolinguals have shown a right-hemisphere advantage (Metuki, Sinkevich, & Lavidor, 2013). Metuki et al suggested that language-specific characteristics of Hebrew, which influence lateralization of semantic processing in Hebrew, influenced the way the bilingual participants processed the task in English.…”
Section: Language Representation In the Brains Of Multilingualsmentioning
confidence: 99%